Enhancing Vocational High School Students’ Technical Skills Through Automation Pneumatic Control Training in The Era of Industry 4.0 - Ikhwan Taufik; Xander Salahudin; Setya Drana Harry Putra; Muktivani Swastiko; Elvi Nur Hikmahwati; Andreas Novean Tejo Setyanto; M. Fendy Kussuma Hadi Sufyan (SPEKTA (Jurnal Pengabdian Kepada Masyarakat : Teknologi dan Aplikasi), 2026)
Background: The current demands of Industry Revolution 4.0 require highly skilled vocational graduates who are skilled in the fundamental technology of automation, including pneumatic control systems. Meanwhile, SMKN 1 Windusari Mechanical Engineering have competency shortage as the school does not have physical equipment in the form of trainer kits in the field of electropneumatic. Contribution: The aim is to improve the technical skill and competency level of students in the control pneumatic systems to be able to meet industry demands as a requisite baseline of smart automation in the Industry 4.0 era. Method: Basically, this program used measurable training methodology, simulation, and hands-on. But the course process involves three stages: situation analysis, preparation, intensive and measured training (1st day: seminar, 2nd day: practical training, simulation), then evaluation and projected outcomes. Results: In quantitative terms, the program realized a gain in knowledge for the students, with the average test score increasing from 66.67 to 72.00 (grade 0-100). Qualitatively, the students can make some electro-pneumatic circuits, like stamping unit, vertical inventory, conveyor line separator, vertical inventory to storage, etc. Conclusion: This Community Service Program has successfully addressed its primary objective: the enhancement of technical competencies in pneumatic control systems as a fundamental element of smart automation in the Industry 4.0 era among SMKN 1 Windusari students.